2018
DOI: 10.3892/or.2018.6221
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the CDK4/6 inhibitor palbociclib (PD 0332991) and its future application in cancer treatment (Review)

Abstract: An uncontrolled cell cycle is an obvious marker of tumor cells. The G1‑S phase is an important restriction point in the normal cell cycle, but in cancer cells the restriction function is reduced, leading to uncontrolled cell proliferation. Two cyclin‑dependent kinases (CDKs), CDK4 and CDK6, play a crucial role in the G1‑S phase transition. Inhibitors of CDK4/6 are presently the subjects of numerous studies, and PD 0332991, an inhibitor of CDK4/6, has been used to treat hormone receptor (HR)‑positive, advanced‑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 76 publications
3
51
0
2
Order By: Relevance
“…Furthermore, a significant upregulation of ATG4A and ATG4D (proteins involved in autophagic cell death) was observed in the shFBXO2 group compared with the RL95-2-NC group ( Figure 7C ). We also found that inhibition of cyclin-dependent kinases by palbociclib (PD0332991, which specifically inhibits cyclin-dependent kinases 4 and 6 [CDK4/6]) ( Liu et al, 2018 ) reversed the effects of FBXO2 on proliferation of Ishikawa cells ( Figure 7D ). We also showed that the inhibition of 3-methyladenine (3-MA, an autophagy specific inhibitor) ( Luan et al, 2019 ) reversed the effects of FBXO2 on proliferation of RL95-2 cells ( Figure 7E ).…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, a significant upregulation of ATG4A and ATG4D (proteins involved in autophagic cell death) was observed in the shFBXO2 group compared with the RL95-2-NC group ( Figure 7C ). We also found that inhibition of cyclin-dependent kinases by palbociclib (PD0332991, which specifically inhibits cyclin-dependent kinases 4 and 6 [CDK4/6]) ( Liu et al, 2018 ) reversed the effects of FBXO2 on proliferation of Ishikawa cells ( Figure 7D ). We also showed that the inhibition of 3-methyladenine (3-MA, an autophagy specific inhibitor) ( Luan et al, 2019 ) reversed the effects of FBXO2 on proliferation of RL95-2 cells ( Figure 7E ).…”
Section: Resultsmentioning
confidence: 78%
“…In tumor cells, an uncontrolled cell cycle is a significant indicator and the restriction function of the G1-S phase check point is reduced in cancer cells, which often leads to uncontrolled cell proliferation [ 24 ]. The data revealed that AsA decreased cyclin D, CDK4, p-RB and induced significant G0/G1-phase accumulation compared with the control in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The transition of G1 to S phase is a key step in the cell cycle process and plays an important role in developing most of the tumors. Suppressing G1/S transition may provide an attractive therapeutic target to stop cancer cells from proliferating [28]. Previously, a study reported that the down-regulation of cyclin H-CDK7 was implicated in the arrest of liver cancer cells in the G1 phase [29].…”
Section: Discussionmentioning
confidence: 99%